2015
DOI: 10.1016/j.dld.2014.07.170
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of statins for the treatment of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease is an emerging liver disease in Western countries and the most frequent cause of incidental elevation of serum liver enzymes. Dyslipidaemia is frequently observed in patients with non-alcoholic fatty liver disease, and treatment of dyslipidaemia plays a critical role in the overall management of these patients. Moreover, coronary artery disease remains the most common cause of death. Statins are effective lipid-lowering agents, associated with a lowering the risk of cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 64 publications
4
107
0
8
Order By: Relevance
“…Our study also showed that there is no significant elevation of liver enzymes in statin group as feared due to the rare and dose related hepatotoxicity of statin. Some studies also showed that statins can cause diabetes mellitus and glucose intolerance, but in our study group all were DM-2 and they did not show elevated HbA1c levels as compared to non statin group [27][28][29][30] .…”
Section: Jmscr Vol||05||issue||03||page 18698-18708||march 2017mentioning
confidence: 70%
“…Our study also showed that there is no significant elevation of liver enzymes in statin group as feared due to the rare and dose related hepatotoxicity of statin. Some studies also showed that statins can cause diabetes mellitus and glucose intolerance, but in our study group all were DM-2 and they did not show elevated HbA1c levels as compared to non statin group [27][28][29][30] .…”
Section: Jmscr Vol||05||issue||03||page 18698-18708||march 2017mentioning
confidence: 70%
“…It was found that only 0.1% patients had severe ALT levels and most importantly severity was associated with drug-drug interactions. [49] Below Table 2 describes the relation between statins and liver abnormalities [48] Taking into account the anti-inflammatory and anti-thrombotic effects property of statins, it is believed that statins may exert beneficial effects in reducing liver cancer, decreasing fibrosis or fatty deposition and improvement of portal hypertension. In a recent Cochrane meta-analysis, statins were found to improve serum aminotransferase levels in NAFLD and NASH; however no effect was observed on histological level and liver-related mortality and morbidity.…”
Section: Cholesterol Statin and Brain Diseasementioning
confidence: 99%
“…In a recent Cochrane meta-analysis, statins were found to improve serum aminotransferase levels in NAFLD and NASH; however no effect was observed on histological level and liver-related mortality and morbidity. [48] Cholesterol, statins and steroid hormones: There are three classes of steroid hormones in mammals namely glucocorticoids, mineralocorticoids, and adrenal androgens. These can be further categorized as adrenal steroid hormones [like cortisol, aldosterone and DHEA(s)] and non-adrenal steroid hormones (like testosterone, progesterone and estradiol).…”
Section: Cholesterol Statin and Brain Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In spite of its potential to drastically reduce lipid levels, the use of fibrates or statins in the clinic is still controversial for treating NASH. 149 30 In this view, anti-oxLDL antibodies can potentially be used as a diagnostic tool for NASH detection. However, it is important to note that the amount of anti-oxLDL antibodies naturally vary between people and can change over time.…”
Section: Clinical Perspectives/implicationsmentioning
confidence: 99%